Nepeta iraqo-iranica (Lamiaceae), a new species from the border of Iraq and Iran - Bordbar, Firouzeh; Haloob, Ali; Qader, Karzan Omar; Mirtadzadini, Mansour (Phytotaxa, 2022)
Nepeta iraqo-iranica, a new species is described and illustrated from NE of Iraq, Sulaimaniya Province, and W of Iran, Kurdistan Province, NW of Bâne. A table of morphological comparison and detailed discussion with morphologically close species is given. The species is considered Critically Endangered (CR) according to IUCN criteria.